Analgesic Use Following Bilateral Breast Reduction. Issue 2 (August 2020) - Fisher, Alec H.; Powelson, Ian A.; Wampler, Ariel T.; Doughty, Hayden; Freed, Gary L.
Abstract : Abstract: The opioid epidemic in the United States resulted in 42, 000 deaths in 2016, 40% of which involved a prescription opioid. It is estimated that 2 million patients become opioid-dependent after elective, ambulatory surgery each year. There has been increased interest in quantifying the need for postoperative narcotic pain medications for a variety of surgical procedures. However, studies have been limited. We sought to quantify the analgesic usage after one of the most common operations performed in plastic surgery, bilateral breast reduction. In this prospective, observational study, sequential breast reduction patients were contacted by telephone on the evening of postoperative days 3 and 7. Patients were queried as to which analgesic medications were used on the day of the phone call. Data relating to dosage, frequency, and satisfaction with pain control were sought. Patients taking chronic narcotics, postoperative complications requiring surgical intervention, and those unable to be reached after multiple attempts were excluded. Complete data were obtained for 40 patients. Narcotic prescriptions were written for oxycodone, hydromorphone and tramadol, with the number prescribed ranging from 0 to 20 tablets. The median total number used was 6 tablets. Eighty percent of patients used a total of 10 tablets or less. Fifty percent of patients were using only nonnarcotic analgesia by postoperative day 3. Patient-reported satisfaction with pain control was overwhelmingly positive, with 95% being either somewhat satisfied or very satisfied with postoperative pain control. Of those taking any medication on postoperative day 3, only half were using a nonsteroidal anti-inflammatory drug (NSAID) as part of their pain regimen. The number of tablets prescribed after breast reduction surgery varies considerably, and there is no consensus regarding the appropriate number to prescribe. Currently, few patients use all the medication prescribed to them, indicating a high rate of overprescribing. The overwhelming majority are satisfied with their pain control. Most patients use less than 10 tablets of narcotic pain medication after surgery. Acetaminophen is widely used as an adjunct but NSAIDs remain underutilized. Based on these data, we recommend that breast reduction patient's pain is best managed with acetaminophen, NSAIDs, and expectation management.